‘Empowerment in Practice and Its Impact on Political Participation’: A Study Among Working Women of South Kolkata - Chatterjee, Anasua (Kultura-Społeczeństwo-Edukacja, 2020)
The main purpose of the present study is to understand ‘empowerment’ as observed in theory and in actual practice in the society where women are still regarded as second-class citizens inspite of achieving success in their chosen fields. Her freedom in choice of decision-making within the family and civil society plays an important part in influencing her participation in politics and her voting behaviour. By political activism of the respondent we primarily mean her cognitive orientation (i.e. her knowledge about political parties, symbols, their stay in power and their judgements about political system), evaluative orientation on how political system works including her voting behaviour and partisan preference. Survey was carried by the researcher on 1000 women working in both the organised and unorganised sectors of the economy mainly among street vendors and domestic workers and bank employees and teachers in Kolkata. Results: Women working in both the sectors play dual role looking after their children, elders in the family, husbands and also contribute to the expenditure but lack effective power in decision-making. They consult their husbands, elder members of the family or the community before casting their vote and are notguided by individual preference or choice.